2020
DOI: 10.1007/jhep01(2020)006
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of compact oscillons

Abstract: We study various aspects of the scattering of generalized compact oscillons in the signum-Gordon model in (1+1) dimensions. Using covariance of the model we construct traveling oscillons and study their interactions and the dependence of these interactions on the oscillons' initial velocities and their relative phases. The scattering processes transform the two incoming oscillons into two outgoing ones and lead to the generation of extra oscillons which appear in the form of jet-like cascades. Such cascades va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 39 publications
(59 reference statements)
0
14
0
Order By: Relevance
“…However, this situation has changed after getting the first results of scattering of high speed oscillons, see Ref. [18]. We have found that such oscillons produce radiation that mainly consists of perturbed oscillons.…”
Section: A the Solutionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, this situation has changed after getting the first results of scattering of high speed oscillons, see Ref. [18]. We have found that such oscillons produce radiation that mainly consists of perturbed oscillons.…”
Section: A the Solutionmentioning
confidence: 98%
“…An interesting question about the oscillons is whether the oscillons may arise in the collision process of kinks, skyrmions and other topological or non-topologigal objects. Recently we have looked at the process of scattering of the signum-Gordon oscillons and emission of a radiation which, as reported in [18], is dominated by a huge number of smaller oscillons. Motivated by this study we have looked in more detail at the process of a collapse of the signum-Gordon shock waves which turns out to be an efficient process of production of oscillons.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The scattering of generalized compact oscillons in the signum-Gordon model were studied in the Ref. [73], showing the generation of oscillons in the form of jet-like cascates.…”
Section: (): V-volmentioning
confidence: 99%
“…However, the first one is characterized by a high amplitude, and its exact structure is still unknown, while the second one has a small amplitude, and its structure is well-known and has a form of a Gaussian. Originally, they were introduced in (1 + 3) dimensions [190] in the ϕ 4 model, later they were implemented for lower dimensions [191] and some other models, e.g., the signum-Gordon model [192]. Usually, oscillons are used as ansatz [70,71], however, the appearance of oscillons was observed beforehand for the sinh-deformed (1 + 1)-dimensional ϕ 4 model [74] after the procedure of a model deformation [72,73].…”
Section: Resultsmentioning
confidence: 99%